2019
DOI: 10.1002/mus.26418
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound appears to be a reliable technique for the diagnosis of piriformis syndrome

Abstract: Introduction : Piriformis muscle syndrome (PS) is a disorder encompassing a constellation of symptoms, including buttock and hip pain. In this study we aimed to assess the value of ultrasound (US) in the diagnosis of PS. Methods : Thirty‐three clinically diagnosed PS patients and 26 healthy volunteers underwent a clinical PS scoring examination and US and MRI assessment of the bilateral piriformis muscles. The areas under the receiver operating characteristic curves (AUROCs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
2
21
0
3
Order By: Relevance
“…The article of Zhang et al in this issue provides evidence for the reliability of ultrasound in the diagnosis of piriformis syndrome, and thus may be of value in the assessment of many patients with sciatica. Some researchers have suggested that piriformis syndrome (PS) is at least as common a cause of sciatica as is disc herniation .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The article of Zhang et al in this issue provides evidence for the reliability of ultrasound in the diagnosis of piriformis syndrome, and thus may be of value in the assessment of many patients with sciatica. Some researchers have suggested that piriformis syndrome (PS) is at least as common a cause of sciatica as is disc herniation .…”
mentioning
confidence: 99%
“…Conversely, negative findings on these methods provide powerful evidence against PS. (1) Ultrasound (US) appears to provide an inexpensive and accurate diagnosis available to a large population. (2) Magnetic resonance neurography (MRN) delineates the sciatic nerve, the piriformis muscle, and a good deal of surrounding anatomy .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Piriformis syndrome is a controversial entity, postulated to cause sciatic nerve compression due to asymmetric hypertrophy or variant anatomy. MRI or US finding of asymmetric piriformis muscle hypertrophy in addition to clinical symptoms is needed to diagnose this entity since asymmetric hypertrophy of piriformis can also be a normal variant [20][21][22]. The affected sciatic nerve may also show thickening on MRI/US and signal alteration on MRI.…”
Section: Imagingmentioning
confidence: 99%